2022
DOI: 10.3390/met12020212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interpass Temperature on Wire Arc Additive Manufacturing Using High-Strength Metal-Cored Wire

Abstract: Wire arc additive manufacturing (WAAM) is suitable to fabricate large components because of its high deposition rate. In this study, a metal-cored low-alloy high-strength welding filler metal was used as feedstock. Single wall structures were prepared using the WAAM process with different interpass temperatures (150 °C, 350 °C, and 600 °C). No obvious microstructure change was observed when the alloy was deposited with the interpass temperatures of 150 °C and 350 °C. Electron backscattered diffraction analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Maintaining the interpass temperature within a suitable range is crucial when influencing microstructures and mechanical properties. There have been studies on a variety of different alloys related to the effect of interpass temperature in WAAM on grain size, phase constitution, and mechanical properties [17][18][19][20][21]. In our work, a pyrometer Metis M318 was used to keep the interpass temperature of the walls below 200 • C. Initially, a single-bead wall, 100 mm in length, was printed for 3 layers in order to screen the processing parameters (i.e., WFS and TS) in the medium-to-high production domain and in turn to ensure a high-quality build free of waviness and with other types of defects kept to a minimum by scanning electron microscopy (Figure 1a).…”
Section: Process Parameter Developmentmentioning
confidence: 99%
“…Maintaining the interpass temperature within a suitable range is crucial when influencing microstructures and mechanical properties. There have been studies on a variety of different alloys related to the effect of interpass temperature in WAAM on grain size, phase constitution, and mechanical properties [17][18][19][20][21]. In our work, a pyrometer Metis M318 was used to keep the interpass temperature of the walls below 200 • C. Initially, a single-bead wall, 100 mm in length, was printed for 3 layers in order to screen the processing parameters (i.e., WFS and TS) in the medium-to-high production domain and in turn to ensure a high-quality build free of waviness and with other types of defects kept to a minimum by scanning electron microscopy (Figure 1a).…”
Section: Process Parameter Developmentmentioning
confidence: 99%
“…Yang et al [18] found that increasing the inter-layer cooling time decreases the height variation in the thin walls, however, excessive dwell time cannot decrease the heat accumulation efficiently and will make the deposition process time-consuming. Maintaining a steady interpass temperature between two consecutive layers resulted in homogeneous microstructure and mechanical properties for HSLA steel walls [19].…”
Section: Bead Height Referencesmentioning
confidence: 99%
“…Though, depending on its geometry, the metallic deposition planning stage has a signi cant impact on the performance of the component produced by WAAM. Some methods to guarantee the geometric precision and adequate mechanical properties of manufactured parts are the use of deposition trajectories that avoid thermal distortions or other geometric defects like pores [17], and the thermal monitoring and control of the component during its manufacturing process [7,[18][19][20]. The heat generated can be dissipated by conduction through the structure and substrate, by forced convection by the shielding gas, or by radiation to the environment.…”
Section: Introductionmentioning
confidence: 99%